New Superior Varieties of Baroma and Nutrizinc Rice Seeds in West Tanjung Jabung Regency, Jambi Province - Bobihoe, Julistia; Endrizal, Endrizal (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2022)
Seeds are an essential means of agricultural production, as well as being a carrier of technological change. The increase in rice production was caused by using superior varieties accompanied by better cultivation techniques compared to previous times. However, currently, superior and quality rice seeds are not available at planting locations, which can be realized based on applied science in the field of agriculture. The aim of the study is to build and open up rice seed business opportunities that can increase the productivity of rice plants and the income of breeder farmers. The New Superior Varieties used in this activity are VUB Baroma and Inpari Nutri Zinc FS/White label. The results of the study showed that the Baroma variety obtained a production of 6.9 t/ha, of which 4.5 tonnes of seed could be used, and the Inpari Nutri Zinc variety obtained a yield of 5.686 tonnes/ha, of which 3.2 tonnes of yield could be used as seed. The results of the farming analysis show that if the Baroma variety is used as seed, a profit of Rp. 35,420,000 with an R/C ratio of 4.69 and the Inpari Nutri Zinc variety, if used as seed, makes a profit of Rp. 29,420,000 with an R/C ratio of 4.07. The VUB Baroma rice seed farming business and Inpari Nutri Zinc provide higher profits than the consumption farming business with the difference between Baroma and Inpari Nutri Zinc profits each being IDR. 11,600,000/ha.